Possible hemoglobin enhancing effect of phytol in methotrexate-induced folate deficient Swiss albino mice: In vivo and in silico studies - Muhammad Torequl Islam; Raihan Chowdhury; Md Sakib Al Hasan; Salehin Sheikh; Md Shimul Bhuia; Sumaya Akter Bithi; Most Israt Jahan Oni; Mehedi Hasan Bappi; Siddique Akber Ansari; Elaine C.P. Lucetti; Catarina M. Tahim; Henrique Douglas Melo Coutinho; et al. (Elsevier, 2024)
The diterpenoid phytol is evidently acting against anemia in experimental animals. However, the molecular mechanisms behind this issue are yet to be discovered. This study aimed to evaluate phytol's effect on methotrexate-induced folate-deficient animals through in vivo and in silico studies. For this, a total of thirty adult male Swiss albino mice were randomly divided into six different groups, namely the normal control (vehicle), the negative control (folate deficiency inducer, methotrexate 3 ​mg/kg), the standard (folic acid 1.5 ​mg/kg), two test groups comprising phytol 25 and 50 ​mg/kg, and a combined group composed of the standard and highest test doses of phytol. Except for the vehicle, all groups were treated with methotrexate for the first 3 days (once/day) to induce folate deficiency. Then followed by the respective treatment once a day for 3 days. Hemoglobin (Hb) level was measured from the peripheral blood (by tail cutting) on days 1st (before treatment), 4th (after methotrexate treatment), and 7th (after treatment). On the other hand, the computational studies were performed by PyMol, PyRex, Discovery Studio, and other complementary tools. Findings suggest that phytol significantly (p ​< ​0.05) augmented Hb levels that are altered by methotrexate-induced reduction of Hb levels in animals dose-dependently. The combination also augmented Hb levels in animals; however, its effect was slightly lower than the individual groups (standard and test). In the in silico study, phytol showed good binding capacity (binding energy: −7.0 ​kcal/mol) with dihydrofolate reductase (DHFR). In conclusion, phytol may act against folate deficiency by altering methotrexate's impacts in animals, possibly through interacting with DHFR. Further validated research is necessary to develop phytol as an anti-anemia drug in the near future.